Journal of Industrial and Business Economics Economia e Politica Industriale - Cambini, Carlo; Colombo, Massimo G.; Piscitello, Lucia; Rondi, Laura; Zanfei, Antonello; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
This peer-reviewed journal, established in 1973 and owned by the Associazione Amici di Economia e Politica Industriale, focuses on firm and industrial organization, innovation, technological change, internationalization, new industries, regulation and industrial policy. It publishes research papers in economics and management that display a sound theoretical background and rigorous (quantitative and qualitative) methodology, as well as case studies and experimental and mixed method studies. Occasionally, the journal publishes symposia and qualified surveys documenting the state of the art in special topics. The journal appeals to scholars, decision-makers, and economists in private and public institutions and encourages submissions dealing with the structure, evolution, and institutional aspects of industries. Firm-level and sectoral-level analyses are most welcome, while the geographic scope may vary from subnational regions to nations, with specific attention to Europe. The major topics are: industrial organization and policy; innovation, entrepreneurship, and industrial dynamics; international economics and business; firm strategy and organization; infrastructures, networks, and regulation; institutions and competition policy; small business; corporate governance and finance; regional development, industrial districts, and economic geography; creative and cultural industries; and environment, sustainability, and socially oriented firms.
Keywords: Entrepreneurship; Leadership; Industrial organization; Economic policy; Industrial Organization; R & D/Technology Policy; Entrepreneurship; Business Strategy/Leadership.